Meta-Analysis Study: Effectiveness of Using GeoGebra on Students' Mathematical Ability - Anajihah, Novita Maharani; Sulistyowati, Fitria; Harini, Esti; Agustito, Denik; Nugraheni, Zahra (Universitas Sarjanawiyata Tamansiswa, 2025)
The use of GeoGebra in mathematics education positively impacts students' mathematical abilities. This meta-analysis examines its overall effectiveness using 10 studies selected from Google Scholar and Scopus based on inclusion criteria. Data were analyzed using RStudio, revealing an overall effect size of 1.31, indicating a highly positive impact. The study also analyzed variability with four moderator variables: education level, publication type, control class type, and mathematical ability. Results show that GeoGebra significantly enhances mathematical abilities based on publication source and control type but is not influenced by education level. Notably, GeoGebra effectively improves students' conceptual understanding of mathematics, making it a valuable tool for enhancing mathematical skills in education. These findings emphasize the significant role of GeoGebra in fostering students' mathematical comprehension.